Fishers' perceptions of the performance of hilsa shad (Tenualosa ilisha) sanctuaries in Bangladesh. (October 2016) - Islam, Mohammad Mahmudul; Islam, Naimul; Sunny, Atiqur Rahman; Jentoft, Svein; Ullah, Md Hadayet; Sharifuzzaman, S.M.
Abstract: A sanctuary is a specific form of protected area and considered to be an important management measure for the conservation and management of fisheries resources. Using socioeconomic and biological indicators, this study investigates the perceptions of fishers towards sanctuaries that were established in the rivers of Meghna and Padma and in inshore waters of Bangladesh since 2005 to protect the declining hilsa ( Tenualosa ilisha ) populations. Both qualitative and quantitative data were collected from six communities adjacent to five hilsa sanctuaries and then analyzed to know the socioeconomic profile of fishers as well as their perceptions of the performance of sanctuaries. The majority of fishers felt that an apparent recent increase in hilsa catch is due to the establishment of sanctuaries. Their perception is well supported by catch statistics that show higher overall hilsa production both from inland and marine waters. However, fishery closure led to substantial economic hardship due to lost income. If the sanctuaries are to function effectively, issues (e.g. lost income) affecting fishers must be addressed by offering compensation schemes so that fishers are able to support their families. The process has to be transparent, inclusive and equitable. There is also a need to support alternative livelihoods for fishers in order to reduce dependence on hilsa fishing. Moreover, fishers must be provided with economic and/or other incentives so as to share responsibilities to protect and manage sanctuaries successfully. Since fishers' involvement is key to the success of sanctuaries, social acceptance of fish sanctuaries by fishers is a must. Highlights: The establishment of sanctuaries is an important attempt to manage the single most important hilsa fishery in Bangladesh. Hilsa fishers need to be involved in the management process in order to make conservation efforts successful. To make the sanctuaries more successful, development programmes should aim to create new economic opportunities for fishers.